Separation of oil/water emulsion using nano-particle (TiO2 - Yi, X. S. (Water Science and Technology)
In the present study, nano-sized TiO2/Al2O3 modified polyvinylidene fluoride (PVDF) membranes (MM) were fabricated and then utilized for oil/water emulsion separation. The results showed that, compared with PVDF membrane (OM), the contact angle of MM decreased and hydrophilicity increased. The ultrafiltration (UF) of oil in water emulsions with transmembrane pressure (TMP) increasing results in a sharp fall in relative flux with time. The cake filtration models did not always predict the performance over the complete range of filtration times very well. In the initial 30 min, all the four cake models can simulate this UF process to a certain extent, and the suitability was: cake filtration > intermediate pore blocking > standard pore blocking > complete pore blocking models. However, they were no longer adapted well with UF time extent to 60 min, but only cake filtration (R2 = 0.9535) maintained a high adaptability. Surface and cross-sectional morphology of the membrane was investigated by SEM to make an advanced certificate of this UF mechanism.